(untitled) (Journal of Muhammadiyah’s Application Technology, 2026)
Sand and gravel mining activities may alter river flow characteristics and sediment transport processes. The Maros River in Tombolo Hamlet is one of the rivers affected by intensive material extraction. This study aims to analyze the characteristics of suspended load and bed-load sediment transport and to evaluate the impact of sand and gravel mining activities on sediment transport in the maros river, Tombolo Hamlet. The research employed field measurements and laboratory analyses of river cross section geometry, flow velocity, discharge, and sediment sampling. Suspended sediment transport was calculated using the instantaneous method, while bed-load sediment transport was analyzed using the Einstein, Meyer Peter muller, and Duboys methods. The results indicate that suspended sediment transport varies and is influenced by flow velocity. Bed-load transport estimates differ among the applied methods, with the Du-boys method producing higher sediment transport rates than the other methods. The flow conditions are classified as turbulent, and the calculated bed shear stress exceeds the critical shear stress, indicating active bed sediment movement. These findings demonstrate that sand and gravel mining activities influence sediment transport characteristics in the maros River, Tombolo Hamlet